ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PENGGUNA TERHADAP APLIKASI PERPUSTAKAAN DIGITAL: STUDI KASUS SEKOLAH TINGGI ILMU EKONOMI INDONESIA BANKING SCHOOL - Deni Wardani (Indonesia Banking School, 2015)
Implementation of information technology in an organization will certainly give a reaction to its users, it can be acceptance or rejection of these technology. Applications Digital Library is a facility that provides a collection of information in digital format. Indonesia Banking School implemented the Digital Library applications in early 2012. Based on user's activity data on January-June 2012, there is indication of the low acceptance of the user (use acceptance) to the digital library applications. Those makes the researchers wanted to know what are the factors that inffluence users to use digital library application.The research design was the modification model of the Unified Theory of Acceptance and Use of Technology (UTAUT) and combined with the model Academic Discipline based Unified Theory of Acceptance and Use of Technology (ADUTAUT). Methods of data collection using questionnaires, while the data processing and decision making used Structural Equation Modelling (SEM) using Lisrel.The result factors that affects users using digital library application are preceived of usefulness, preceived of ease of use, and preceived of faciltating condition.Keywords: Digital Application Library, UTAUT, ADUTAUT, Structural Equation Modelling.